lec0229 - Some Algebra Rules Laws of exponent and Logarithm...

This preview shows pages 1–5. Sign up to view the full content.

Some Algebra Rules ... Laws of exponent and Logarithm: If a > 0, a x a y = a x + y ( a x ) y = a xy a x / a y = a x y a x = 1 / ( a x ) If b > 0 and b 1, log b ( xy ) = log b x + log b y log b ( x / y ) = log b x log b y log b ( x p ) = p log b x . Rules of inequalities: a > b a + c > b + c if c > 0, then a > b a c > b c if a > b and b > c a > c ; if a > b and c > d a + c > b + d . Useful algebra rules: ab = 0 a = 0 or b = 0 if bd 0, then a / b = c / d ad = bc ; ( a + b ) 2 = a 2 + 2 ab + b 2 ; ( a + b )( a b ) = a 2 b 2 .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
A couple of summation rules = n i i f 1 ) ( = = m i i f 1 ) ( + + = n m i i f 1 ) ( , if 1 m < n. = b a i i f ) ( = = b i i f 1 ) ( - - = 1 1 ) ( a i i f , if b a > 1. = n i i f 1 ) ( = = - + n i i n f 1 ) 1 (
Prove by induction that n ! > 2 n for all n 4. (Note: n ! = n ( n 1)···2·1, for n 1; 0! = 1 by convention.) Proof: We use induction on n 4. (Basis Step) Consider n = 4. In this case, n ! = 4! = 4·3·2·1 = 24, and 2 n = 2 4 = 16 < 24. So the Basis Step is proved. (Induction Hypothesis) Consider the statement for an arbitrary value of n. Suppose n ! > 2 n for some n 4. (Induction Step) Consider the statement for n+1. We need to prove ( n + 1)! > 2 n +1 ( n + 1)! = ( n + 1) · n !, > ( n + 1) ·2 n , by the Induction Hypothesis > 2 ·2 n , because n + 1 5 > 2 = 2 n +1 . By induction, we have proved the inequality n ! > 2 n for all n 4.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Inductively (Recursively) Defined Objects The induction principles can be used to define structures in terms of themselves, usually “smaller” in size. We first consider recursively defined functions. For example, to define the Factorial function n !, where n is a natural number, 0! = 1 n ! = n · ( n – 1)!, for n > 0. So, we can compute the following using the recursive definition: 1! = 1 · (1 – 1)! = 1 · 0! = 1 · 1 = 1.
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

What students are saying

• As a current student on this bumpy collegiate pathway, I stumbled upon Course Hero, where I can find study resources for nearly all my courses, get online help from tutors 24/7, and even share my old projects, papers, and lecture notes with other students.

Kiran Temple University Fox School of Business ‘17, Course Hero Intern

• I cannot even describe how much Course Hero helped me this summer. It’s truly become something I can always rely on and help me. In the end, I was not only able to survive summer classes, but I was able to thrive thanks to Course Hero.

Dana University of Pennsylvania ‘17, Course Hero Intern

• The ability to access any university’s resources through Course Hero proved invaluable in my case. I was behind on Tulane coursework and actually used UCLA’s materials to help me move forward and get everything together on time.

Jill Tulane University ‘16, Course Hero Intern